Grand corruption in the global south: Legal, political and economic analysis of assets recovery in Nigeria - Simeon A. Igbinedion; Anthony Osobase (Journal of Economic Criminology)
This paper examines the battle against grand corruption in the Global South (with special emphasis on Nigeria) from the multi-disciplinary perspectives of law, politics and economics. Because grand corruption is a crime, the government – acting for the state – has the exclusive jurisdiction to invoke the existing anti-corruption regime against offenders and their illicitly acquired assets. However, the sole reliance on law has proven to be grossly inadequate because the quantum of recovered assets is disproportionately infinitesimal to the much that is plundered. The objective of the paper is to discuss these issues towards the end of narrowing the gap between assets plundered and assets recovered. In view of such legal inadequacy, this paper interrogates the political attributes of grand corruption and the propensity of the political class to promote its interest over and above that of the rest and to frustrate anti-corruption initiatives. Economically, the paper evaluates the crime by using time series data spanning from 2004 to 2021 and multiple regression technique on the data. The outcome suggests that grand corruption indicator has negative significant impact on economic growth in Nigeria. The result of the discussion demonstrates that it is futile to expect law alone to overcome the incidence of grand corruption and, more importantly, facilitate assets recovery. Such result necessitates the deployment of political and economic analyses. In conclusion, the paper suggests some policy measures that could enable Nigeria and, by extension, many other states in the Global South to overcome the economic crime and render the plundering of their collective patrimony highly unattractive to unscrupulous public officials. Surely, such outcome would channel assets that would otherwise have been plundered to human and national development.